2015
DOI: 10.1089/ten.tea.2014.0022
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Heterospheroids of Islet Cells and Mesenchymal Stem Cells for Effective Angiogenesis and Antiapoptosis

Abstract: Although islet transplantation has been suggested as an alternative therapy for type 1 diabetes, there are efficiency concerns that are attributed to poor engraftment of transplanted islets. Hypoxic condition and delayed vasculogenesis induce necrosis and apoptosis of the transplanted islets. To overcome these limitations in islet transplantation, heterospheroids (HSs), which consist of rat islet cells (ICs) and human bone marrow-derived mesenchymal stem cells (hMSCs), were transplanted to the kidney and liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Mesenchymal stem cells have shown many unique functions, including release of trophic factors with diverse effects such as improved tissue repair, the reduction of apoptosis, and the promotion of neovascularization . Therefore, they have been used to provide protection for islets from hypoxia‐mediated cell death in islet transplantation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells have shown many unique functions, including release of trophic factors with diverse effects such as improved tissue repair, the reduction of apoptosis, and the promotion of neovascularization . Therefore, they have been used to provide protection for islets from hypoxia‐mediated cell death in islet transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells have shown many unique functions, including release of trophic factors with diverse effects such as improved tissue repair, the reduction of apoptosis, and the promotion of neovascularization. [40][41][42][43] Therefore, they have been used to provide protection for islets from hypoxia-mediated cell death in islet transplantation. 23,[44][45][46] Some studies showed that MSC co-transplantation had a positive effect on islets to tolerate poor oxygenation, but most of these studies focused on accelerating revascularization, rather than directly combating hypoxic damage.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in islet transplantation in type-1 diabetic patients. The hypoxic response in the transplanted islets may slow their rate decay until revascularized in their new milieu (Linn et al, 2006;Shin et al, 2015).…”
Section: Cellular Defense Mechanism Against Free Radical Stress In Bementioning
confidence: 99%
“…This observation is particularly true when cells are systemically administered because the efficacy of this approach is limited by the quantity of viable cells that reach an injured tissue. [5][6][7] Unfortunately, previous investigations have uniformly demonstrated poor engraftment of transplanted cells. In the absence of ex vivo pretreatment or modification, less than 3% of transplanted cells typically engraft following their introduction into the body.…”
Section: Introductionmentioning
confidence: 99%